FDI and economic growth nexus: An empirical assessment of ECOWAS countries - Aderemi, Timothy A (Asian Economic and Financial Review, 2025)
This study evaluated the effects of FDI on ECOWAS economic growth in ECOWAS countries through time series data between 1990 and 2023. In its assessment, the ARDL approach was employed with the following results: the study found that FDI creates a considerable direct relationship with economic growth. Similarly, economic expansion goes hand in hand with open trading operations. The inflation rate shows a minor negative relationship with the economic expansion rate. The relationship between manufacturing value added shows positive and beneficial impacts on economic growth. The population growth rate shows both positive and considerable effects on economic growth in ECOWAS countries. This scholarly research recommends that policymakers throughout ECOWAS should establish programs to drive FDI inflows into their countries because such measures will create meaningful sub-regional economic growth. The research suggests that ECOWAS lawmakers should implement measures to enhance manufacturing sector growth, which will boost productivity levels while creating jobs for achieving sustainable economic expansion in their nations.